Negative impacts of insecticide-treated methods and slot traps for trapping of Ips cembrae on nontarget invertebrates - Špoula, Jakub; Foit, Jiří; Resnerová, Karolina; Kula, Emanuel (Wiley-Blackwell, 2025)
Background: Ips cembrae is serious forest pest of European larch (Larix decidua). The negative impacts on nontarget invertebrates of the use of different I. cembrae trapping methods has not yet been evaluated, although mortality of nontarget invertebrates may occur. Results: Between 2016 and 2022, the impact of different I. cembrae trapping methods on nontarget invertebrates was assessed. Four trapping methods (slot traps, insecticide-treated tripods, logs and trees) baited with the pheromone lure Cembräwit were tested. Based on larval feeding habits, the captured nontarget invertebrates were grouped into four feeding types: predators, phloexylophagous, saproxylophagous and mycetophagous. The results indicate that predators, especially the clerid beetle Thanasimus formicarius, were the most negatively affected group of nontarget invertebrates. A negative effect on a number of IUCN Red List species also was shown, particularly on Corticeus fraxini (Tenebrionidae). The results show that Cembräwit-baited slot traps capture not only I. cembrae, but also other serious forest pests such as I. sexdentatus and Pityogenes chalcographus. The overall effect of different trapping methods on I. cembrae population densities has not been studied; however, our results indicate that the use of insecticide-treated methods has a negative effect on I. cembrae predators. Conclusion: The negative effect on the predators may be sufficiently large to outweigh any benefits gained from a reduction in I. cembrae numbers resulting from trapping. Therefore, in order to reduce the negative impacts on nontarget invertebrates, properly timed and consistent salvage logging should be used rather than insecticide-treated trapping methods. (C) 2025 The Author(s). Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.
Keywords: Cembräwit; cypermethrin; Larix; saproxylic beetles; insecticide-treated traps; mass trapping